The Impact of Implementing Usability Principles in UI/UX on Consumer Purchase Intention on the Shopee Platform - Nugroho, Doni Tri; Indah, Dwi Rosa; Novianti, Hardini; Sanjaya, M. Rudi; Syahbani, M. Husni (Sistemasi: Jurnal Sistem Informasi, 2025)
The advancement of technology and the internet has transformed consumer behavior, particularly in online shopping through e-commerce. Shopee, as a leading e-commerce platform in Indonesia, accounted for 51% of total e-commerce visits from February to April 2024, thanks to its integration of usability principles in its User Interface (UI) and User Experience (UX). In a highly competitive e-commerce landscape, usability is a key factor influencing purchasing decisions, as an optimal user experience can enhance trust and reduce shopping cart abandonment. This study evaluates the impact of usability, based on Nielsen’s Attributes of Usability (NAU), on consumer purchase intention on Shopee. A quantitative survey method was employed, involving 100 active Shopee users in Palembang. Data was collected through an online questionnaire and analyzed using multiple linear regression. The results indicate that efficiency, memorability, and satisfaction significantly influence purchase intention, with efficiency having a negative impact, while memorability and satisfaction have positive effects. Meanwhile, learnability and errors were found to have no significant effect. From a practical perspective, Shopee and other e-commerce platforms should optimize memorability and satisfaction in UI/UX design—such as through personalized interfaces and enhanced accessibility—to improve user experience, drive purchase intention, and strengthen customer loyalty in an increasingly competitive market.